2008
DOI: 10.2224/sbp.2008.36.8.1035
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Sexual Information Sources, and Sexual Attitudes and Behaviors of University Students in Turkey

Abstract: Gender differences in sexual information sources and sexual attitudes and behaviors of college students in Turkey were examined. Results show that the attitudes and behaviors of Turkish college students as regards sexuality are becoming more liberal, although the conservative culture still has some effects, especially concerning gender differences. Sources of sexual information have increased as a result of technological advances, and usage of these differs according to gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
8
0
3
Order By: Relevance
“…Past studies with Turkish college students established similar rates for men (e.g., Aras, Orcin, Ozan, & Semin, 2007;Boratav & Çavdar, 2012) but lower rates for women (e.g., Aras et al, 2007;Golbasi, Erenel, & Tugut, 2012). The higher number of sexually experienced women in the present sample may be related to a liberalization of sexual behaviors and attitudes among Turkish college students in recent years (see Gelbal et al, 2008). The average age at first sexual intercourse in the present sample was 18.3 years for men and 19.1 years for women, which was similar to past findings from Turkey (Aras et al, 2007;Ege, Akin, Kültür Can, & Ariöz, 2011;Eşsizoğlu, Yasan, Yildirim, Gurgen, & Ozkan, 2011).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Past studies with Turkish college students established similar rates for men (e.g., Aras, Orcin, Ozan, & Semin, 2007;Boratav & Çavdar, 2012) but lower rates for women (e.g., Aras et al, 2007;Golbasi, Erenel, & Tugut, 2012). The higher number of sexually experienced women in the present sample may be related to a liberalization of sexual behaviors and attitudes among Turkish college students in recent years (see Gelbal et al, 2008). The average age at first sexual intercourse in the present sample was 18.3 years for men and 19.1 years for women, which was similar to past findings from Turkey (Aras et al, 2007;Ege, Akin, Kültür Can, & Ariöz, 2011;Eşsizoğlu, Yasan, Yildirim, Gurgen, & Ozkan, 2011).…”
Section: Discussionsupporting
confidence: 50%
“…This means there is social control over women's bodies and sexuality (Gursoy, McCool, Sahinoglu, & Yavuz Genc, 2016), while there are no restrictions for men (Cok, Gray, & Ersever, 2001). Although recent years have seen a liberalization of sexual lifestyle (Gelbal et al, 2008) and attitudes, in particular among young educated women (Öngen, 2006), and globalization means unrestricted access to portrayals of gender relations and sexual behavior patterns among young people in other parts of the world, conservative social norms about sexuality remain influential (Yalçın, Arıcıoğlu, & Malkoç, 2012). Young people in Turkey are therefore exposed to conflicting influences and messages about sexual relations between men and women, which could contribute to the blurring of boundaries between consensual sex and sexual aggression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the double standards for male and female sexuality and virginity, and traditional myths regarding the hymen are still prevalent (Cok & Gray, 2007;Eşsizoğlu, Yasan, Yildirim, Gurgen, & Ozkan, 2011). The majority of male students approved of premarital sexual intercourse for men but not for women according to the findings in a study by Gelbal, Duyan, and Öztürk (2008). However, Aras, Orcin, Ozan, and Semin (2007) found that male university students disapproved of premarital sex for both sexes.…”
mentioning
confidence: 99%